2020
DOI: 10.1088/1475-7516/2020/03/061
|View full text |Cite
|
Sign up to set email alerts
|

Axion resonances in binary pulsar systems

Abstract: We investigate the extent to which resonances between an oscillating background of ultra-light axion and a binary Keplerian system can affect the motion of the latter. These resonances lead to perturbations in the instantaneous time-of-arrivals, and to secular variations in the period of the binary. While the secular changes at exact resonance have recently been explored, the instantaneous effects have been overlooked. In this paper, we examine the latter using N-body simulations including the external oscilla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For these axions, there exists a primordial Uð1Þ symmetry which is unbroken quite earlier from the inflationary era, but it is broken during the inflationary era. The cosmological implications of the axions have quite appealing features and, in view of the growing research stream that is related with axion experiments and observations ( [12][13][14][15][16][17][18][19][20][21][22] see also [23]), axion physics has become quite timely. Actually, the axion may be one of the last realistic weakly interacting massive particles (WIMP) [24], since a longstanding number of experiments focusing on large WIMP masses ended up with no result.…”
Section: Introductionmentioning
confidence: 99%
“…For these axions, there exists a primordial Uð1Þ symmetry which is unbroken quite earlier from the inflationary era, but it is broken during the inflationary era. The cosmological implications of the axions have quite appealing features and, in view of the growing research stream that is related with axion experiments and observations ( [12][13][14][15][16][17][18][19][20][21][22] see also [23]), axion physics has become quite timely. Actually, the axion may be one of the last realistic weakly interacting massive particles (WIMP) [24], since a longstanding number of experiments focusing on large WIMP masses ended up with no result.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a realistic explanation is that dark matter consists of axions [34][35][36][37][38][39][40][41][42][43][44]. In contrast to failed experiments for WIMPs, there are some indications in favor of the existence of axions (see [45][46][47][48][49][50][51][52]). Axion emission can appears in the process of the cooling of neutron stars [53].…”
Section: R-square Gravity With a Scalar Axion Fieldmentioning
confidence: 99%
“…The gravitational field oscillations, produced by the oscillating DM, look like gravitational waves to an observer on Earth and would be detected in future laser interferometer experiments. An approach based on the observations of binary pulsars was discussed in [29,30] to probe of ultralight axion DM. It was shown that oscillations of DM resonantly perturb the orbits of the binary pulsars thus leading to secular variations in their orbital period.…”
Section: Introductionmentioning
confidence: 99%